Tree diversity and regeneration dynamics toward forest conservation and environmental sustainability: A case study from Nawabganj Sal Forest, Bangladesh - Jubair, Abu Naser Md.; Rahman, Md. Shoaibur; Sarmin, Israt Jahan; Raihan, Asif (Journal of Agriculture Sustainability and Environment, 2023)
The objective of this study was to examine the regeneration dynamics and population structure of the most prevalent tree species, Shorea robusta (Sal), alongside four other dominant tree species (Tectona grandis, Syzygium cumini, Trema orientale, and Cassia fistula) in the Nawabganj Sal Forest in Bangladesh. The regeneration status and tree diversity of all documented tree species were assessed using a simple random sampling technique. Among the 30 species, 5 species (Shorea robusta, Tectona grandis, Trema orientale, Gmelina arborea, and Artocarpus heterophyllus) exhibited favorable regeneration state, whereas 15 species had moderate regeneration status. However, the absence of the condition 'no regeneration' was due to the absence of the adult stage, which resulted in the absence of seedlings and saplings. The quantity of seedlings was greater during the rainy season compared to the dry season. The girth class distribution of Shorea robusta and all other studied tree species combined exhibited a reverse J-shaped population curve. There was a decline in tree density as the girth class increased, and trees with a larger girth class accounted for 34 individuals per hectare, indicating a strong ongoing regeneration capability. The Shannon-Wiener diversity index, Simpson's dominance index, Pielou's evenness index, and Margalaf's species richness index had values of 0.223, 0.937, 0.077, and 2.249, respectively. These values imply a limited diversity of tree species in the examined forest. Shorea robusta has the highest dominance (m²/ha), followed by Tectona grandis (0.091), Syzygium cumini (0.087), Trema orientale (0.022), and Cassia fistula (0.008). The cumulative basal area of the tree species examined amounted to 40.04 m²/ha, with Shorea robusta accounting for 39.81 m²/ha. This indicates that Sal is the prevailing tree species in the forest. Nevertheless, this study offers fundamental data regarding the current condition of the tropical Sal Forest toward forest conservation and environmental sustainability.